2020
DOI: 10.1007/s00784-020-03244-1
|View full text |Cite
|
Sign up to set email alerts
|

CXCL1, CCL2, and CCL5 modulation by microbial and biomechanical signals in periodontal cells and tissues—in vitro and in vivo studies

Abstract: Objectives This study was established to investigate whether the chemokines CXCL1, CCL2, and CCL5 are produced in periodontal cells and tissues and, if so, whether their levels are regulated by microbial and/or mechanical signals. Materials and methods The chemokine expression and protein levels in gingival biopsies from patients with and without periodontitis were analyzed by RT-PCR and immunohistochemistry. The chemokines were also analyzed in gingival biopsies from rats subjected to experimental periodontit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Fibroblasts were treated with F. nucleatum ATCC 25586 (OD 660 : 0.05) for 1 d. The microorganisms had been suspended in phosphate-buffered saline (OD 660 = 1.0, equivalent to 1.2 × 10 9 bacterial cells/mL) and subjected twice to ultra-sonication (160 W for 15 min) before the experiments. Fibroblasts were also subjected to constant tensile strain (CTS) with a cell strain device for 1 d, as in our previous studies ( Figure 7 a,b) [ 60 , 61 , 62 ]. In addition, fibroblasts were exposed simultaneously to F. nucleatum and CTS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibroblasts were treated with F. nucleatum ATCC 25586 (OD 660 : 0.05) for 1 d. The microorganisms had been suspended in phosphate-buffered saline (OD 660 = 1.0, equivalent to 1.2 × 10 9 bacterial cells/mL) and subjected twice to ultra-sonication (160 W for 15 min) before the experiments. Fibroblasts were also subjected to constant tensile strain (CTS) with a cell strain device for 1 d, as in our previous studies ( Figure 7 a,b) [ 60 , 61 , 62 ]. In addition, fibroblasts were exposed simultaneously to F. nucleatum and CTS.…”
Section: Methodsmentioning
confidence: 99%
“…Approval of the Ethics Committee of the University of Bonn and written informed consent from the patients or their parents were obtained (#043/11). Gingival tissues were either stored immediately in RNA stabilization reagent (RNAlater) (Qiagen, Hilden, Germany) and kept in the −80 °C freezer until use or fixed in formaldehyde for histological examination [ 60 , 61 , 63 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…F. nucleatum plays a significant etiopathogenetic role in gingivitis and periodontitis [12][13][14][15][16]. Previous studies by our research group have shown that mechanical/orthodontic forces can regulate the bacteria-induced levels of some proinflammatory and anti-apoptotic molecules [17][18][19]. The synthesis of some of these molecules during periodontal inflammation is further enhanced by mechanical/orthodontic forces, whereas other molecules tend to be downregulated [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, using cytokine antagonists to treat PD in this scope needs to be further examined properly to obtain conclusive and effective treatment modalities. Recently, Rath-Deschner et al reported higher levels of CXCL 1 (motif chemokine ligand 1), CCL 2 (motif chemokine ligand 2), and CCL 5 (motif chemokine ligand 5) chemokines in vitro and in vivo in human and rat gingiva in sites with periodontitis [38]. CXCL 1 , also known as GRO-alpha, is a potent chemoattractant for neutrophils [39], whereas CCL 2 and CCL 5, also known as MCP-1 and RANTES, are primarily responsible for the recruitment of monocytes, macrophages and T-lymphocytes [38].…”
Section: Cytokines Proteases and Prostaglandinsmentioning
confidence: 99%